Effect of Soil –Structure Interaction on Seismic Evaluation of Existing Building Frames Resting on Raft Foundation - Jarallah, Husain Khalaf (Basrah Journal for Engineering Sciences, 2015)
The objective of the present paper is to evaluate the effects of the soil-structure interaction on the seismic evaluation in the building when a framed building is supported on raft foundation. Also the foundation-soil interaction effect has been considered by replacing it with equivalent springs. Nonlinear static pushover analyses of eight-storey reinforced concrete hospital building located at Delhi-India has been performed using the Capacity Spectrum Method of ATC-40. The deformations define the state of damage in the structure through three limit states of the NEHRP Guidelines and the FEMA-356 have been used to evaluate the performance level of the building for drift, the plastic hinge stage of the crack and shear under the condition of the fixed base and the effect of the soil-structure interaction. The performance of the building and individual components has been estimated for Design Basis Earthquake and Maximum Considered Earthquake. The weight of the slab was distributed as triangular and trapezoidal loads to the surrounding beams as per IS 456:2000. The weight of the brick masonry was distributed uniformly on the beams. The results show that the soil structure interaction has marked effect on the roof displacement, storey drift, design base shear, effective damping and crack pattern for beams and columns while there is a minor effect on the torsional behavior of the building. The building is more critical in the performance level when considering the soil flexibility.